2022
DOI: 10.1016/j.hemonc.2021.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Mutation Profile in BCR-ABL1-Negative Myeloproliferative Neoplasms

Abstract: Objective/Background: Recurrent somatic mutations in the JAK2, calreticulin (CALR), and the MPL genes are described as drivers of BCR-ABL1-negative myeloproliferative neoplasms (MPN) that includes polycythemia vera (PV), essential thrombocytosis (ET), primary myelofibrosis (PMF), and MPN unclassified (MPN-U). Methods: We describe the mutation profile and clinical features of MPN cases diagnosed at a tertiary care center. JAK2V617F and MPL (S505/W515) mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
1
3
1
Order By: Relevance
“…We found that CALR positive cases present at a younger age with lower hemoglobin and higher platelet count in ET and PMF. These findings are in concordance with studies conducted by Maddali et al 9 In our study, MPL was found in 3.1% of patients with PMF and 4.4% patients with ET, similar to published data. 14 A comparison of driver mutation analysis with other studies is given in Table 2.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…We found that CALR positive cases present at a younger age with lower hemoglobin and higher platelet count in ET and PMF. These findings are in concordance with studies conducted by Maddali et al 9 In our study, MPL was found in 3.1% of patients with PMF and 4.4% patients with ET, similar to published data. 14 A comparison of driver mutation analysis with other studies is given in Table 2.…”
Section: Discussionsupporting
confidence: 94%
“…This frequency of JAK2 V617F was lower than 71% in a survey conducted by Dixith et al and 68% in a study conducted by Sazawal et al 7,8 The frequency of CALR and MPL was 13.9% and 2%, which correlates with the published data. In this study, JAK2 V617F mutation was noted in 29 patients (65.9%) with PV, which is lower than 90% in a study conducted by Maddali et al 74% in a study conducted by Singh et al and 85% in a study conducted by Yassin et al 3,9,10 A possible reason may be due to the overdiagnosis of JAK2 negative PV. 2016 WHO diagnostic PV criteria were less precise and lacked a separate criterion for labeling JAK2 negative PV.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…The risk of occurrence of complications such as thromboembolic phenomena or the progression to acute myeloid leukemia (AML) differs between these types of MPNs and hence, correct diagnosis is imperative for effective management and long-term follow-up. 6…”
Section: Chroniclementioning
confidence: 99%
“…The risk of occurrence of complications such as thromboembolic phenomena or the progression to acute myeloid leukemia (AML) differs between these types of MPNs and hence, correct diagnosis is imperative for effective management and long-term follow-up. 6 Classical MPNs include three entities, namely, ET, PV, and PMF. Although the clinical features of these entities are different in their typical forms, the majority of the cases have overlapping clinicopathologic and morphologic features; hence, accurate diagnosis is often challenging.…”
Section: Chroniclementioning
confidence: 99%